ASSESSING THE IMPACTS OF REGIONAL INTEGRATION ON INTRA-AFRICA TRADE, MIGRATION PATTERNS, LAND USE, AND SUSTAINABILITY: A CASE STUDY OF THE EAST AFRICAN COMMUNITY - ABRAHAM ENAME MINKO (African Journal on Land Policy and Geospatial Sciences)
The African continent has witnessed a dynamic shift towards regional integration as a strategic pathway to amplify economic growth, social development, and political cooperation. Within this context, the East African Community (EAC) has emerged as a pivotal example of regional integration efforts. Formed by Burundi, Kenya, Rwanda, South Sudan, Tanzania, and Uganda, the EAC aims to facilitate economic collaboration, encourage political stability, and address shared challenges among its member states. The EAC's journey towards integration dates back to its establishment, characterized by the signing of the Treaty for the Establishment of the East African Community in 1999. Since then, the community has undertaken a series of ambitious initiatives, including the establishment of a common market, the implementation of a single customs territory, and the pursuit of harmonized policies across diverse sectors. These endeavors are geared towards fostering intra-regional trade, promoting the movement of labor, enhancing infrastructure connectivity, and collectively addressing pressing issues such as land use and sustainability. The region's history is marked by both synergies and complexities in trade, migration, land utilization, and sustainability practices. Historically, the EAC countries have shared socio-economic ties and cultural bonds, leading to significant trade and labor flows across borders. However, barriers and disparities have also impeded seamless integration, ranging from tariff obstacles to differing land tenure systems and environmental approaches.